Currency Substitution and Financial innovation. (IMF Working Papers; Working Paper, 1989)
This paper presents a cash-in-advance framework, with variable income velocity, where the domestic effects, as well as the international transmission, of financial innovation can be analyzed. In particular, the discussion emphasizes the role of currency substitution and of cross-border transfers of seigniorage in determining the general equilibrium effects of financial innovation.